Phenomenon of Demikhov. In the 1st Moscow Medical Institute named after Sechenov (1956–1960). At the Chair of the Operative Surgery and Topographic Anatomy (1956–1958) - S. P. Glyantsev (Трансплантология (Москва), 2016)
.